Effects of seed treatment on cassava stake performance, whitefly population, disease incidence, and yield performance of cassava (Manihot esculenta Crantz) in Malawi - Nwokoro, Charles Chigemezu; Kachigamba, Donald; Chiipanthenga, Margaret; Klauser, Dominik; Robinson, Mike; Berlin, Robert (Frontiers in Agronomy, 2024)
Whitefly (Bemisia tabaci) is a pest of cassava (Manihot esculenta Crantz) and the vector for two of the crop's major viral diseasescassava mosaic disease (CMD) and cassava brown streak disease (CBSD), causing severe economic losses for farmers. In this context, we conducted an onfarm experiment to study the efficiency of a seed treatment technology containing thiamethoxam, fludioxonil, and metalaxyl for rapid multiplication of superior cassava genotypes and early protection of the crop against whitefly at Salima and Nkhotakota, central Malawi in the 2019/2020 and 2020/2021 cropping seasons, respectively. The trials were conducted using a randomized complete block design with four replicates. The effect of the application of the seed treatment on stake germination, whitefly population, CMD and CBSD incidences, and stem and storage root yields of three cassava varieties (Kalawe, Mbundumali, and Sauti) at three stake sizes (8 cm, 16 cm, and 25 cm) was compared with a controla 25 cm stake size of each of the cassava variety without seed treatment. A benefit-cost analysis was conducted to determine the profitability of the seed treatment technology for each stake size under certified and non-certified stem scenarios.Regardless of stake size and variety, plant germination was highest (96% by 16%) and mean whitefly population lowest (adult 0.4 vs. 3.0 plant -1 ; nymph 1.0 vs. 3.3 plant -1 ) with seed treatment application than without. Disease incidence measurements showed no significant effect of seed treatment on CBSD control (p = 0.31), but it reduced CMD incidence by 17% vs. 20% in the untreated. Stem and storage root yields across stake size and cassava variety were highest with seed treatment; 489 bundles ha -1 and 10 (DM) Mg ha -1 , respectively. Using the 8 cm stake regardless of variety resulted in the highest average benefit-cost ratio for certified (18.3 USD USD - 1 ) and non-certified (7.8 USD USD -1 ) cassava stem scenarios. We conclude that the application of the seed treatment tested in this study would offer protection to planted stakes, increase their germination, reduce whitefly population, increase stem and storage root yields in areas